Semi-detailed survey of soils of Ceará’s semiarid region: Lavoura Seca Experimental Farm - Silva, Ryshardson Geovane; Mota, Jaedson Cláudio; Toma, Raul (Revista Ciência Agronômica, 2020)
The semiarid region of northeastern Brazil has more than 53 million inhabitants who depend, directly or indirectly, on the resources that the region offers. Among these resources, the soil is highlighted as one of the most important. Due to the importance attributed to the knowledge on the pedological and morphological characteristics of the soils of the Brazilian northeastern semiarid region, the aim of this study was to identify and characterize the different soil classes on the Lavoura Seca Experimental Farm, in the municipality of Quixadá, Ceará, Brazil, through the traditional method of soil mapping. The selected site is located in the municipality of Quixadá, Ceará, with a total extension of approximately 190 hectares. A regular grid of 200 m x 200 m was established to determine the sampling sites, totaling 47 collection points. The soil samples were collected with an auger at depths of 0-20, 40-60 and 80-100 cm, and the chemical and granulometric analyses were then carried out to select the pit opening sites and classify the units according to the Brazilian Soil Classification System (SIBCS). The predominant soil classes in the study area were: Neossolos Litólicos Eutróficos típicos (59.4%), Planossolos Háplicos Eutróficos típicos (20.4%), Argissolos Vermelhos Eutróficos típicos and abrúpticos (15.9%) and Luvissolos Crômicos Órticos típicos (4.3%). Differences in parent material, relief and climate were the main influencing factors for the occurrence of a diversity of soil classes in the studied area, which shows large extensions of young and shallow soils, as well as evolved and deep soils.